Posterior reversible encephalopathy syndrome: a diagnostic dilemma - B., Sheetal; Doddamani, Usha; Shali, Sohail; Sangundikar, Pooja H.; Shradha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Incidence of eclampsia 1 in 2000 to 3250. Seizures can occur antepartum, intrapartum, postpartum. PRES characterised by features like visual disturbances, headache, vomiting, seizures and altered sensorium .Hypertension major cause of PRES. Study aims incidence of PRES, asses clinical presentation, neuroimaging in PRES patients and maternal outcome. Methods: PRES is neurological disorder characterized by symptoms like visual disturbances, headache, vomiting, seizures and altered sensorium. Eclampsia by definition have seizures as part of clinical syndrome. In our study, all patients diagnosed with PRES admitted in obstetric ICU from January 2023 to June 2023 at Gulbarga institute of medical sciences are included. They underwent CT scan for diagnosis of PRES. Abnormal findings included brain hypodense areas in posterior parietal lobe and occipital areas, posterior temporal lobes. To avoid misdiagnosis, it requires careful attention to clinical and radiographic presentation. Main criteria for PRES are Presence of neurologic symptoms or findings, presence of risk factors for PRES, absence of other possible causes of encephalopathy, Reversible course on follow up. Results: Out of 22 patients admitted in obstetric ICU, 14 cases revealed PRES on neuroimaging. Eclampsia occurred in 20 antepartum and in 2 postpartum patients. Headache being predominant symptom, followed by altered mental status, visual disturbances. Conclusions: Our study revealed the common finding of PRES in patients with eclampsia which suggested that PRES is a core component of pathogenesis of eclampsia in pregnancy. Hence early diagnosis and treatment is essential to avoid irreversible neurological damage and maternal morbidity and mortality.